Comparison of venous thromboembolism risk stratification models in a high risk otolaryngology patient cohort. Issue 5 (May 2019) - Tham, Tristan; Costantino, Peter
Our objective was to compare the venous thromboembolism outcomes in two of the most commonly utilised venous thromboembolism assessment tools, the Caprini system and the University of Michigan system, in a high risk head and neck surgery population. Currently, there is a lack of data reporting the validation of well known scoring systems in this patient population. Established risk factors for venous thromboembolism were included in the data collection process. We retrospectively evaluated all patients with the Caprini Risk Assessment and the University of Michigan Health System (UMHS) Scores. Out of all the risk factors, only length of surgery was found to be associated with venous thromboembolism. The mean Caprini scores in those with and without venous thromboembolism were 8.00 ± 3.00 and 6.86 ± 1.45, respectively. The mean UMHS scores in those with and without venous thromboembolism were 6.85 ± 1.28 and 6.54 ± 1.20, respectively. Both scoring systems were not found to be associated with venous thromboembolism.